Big and bad: how relative predator size and dietary information influence rusty crayfish (Faxonius rusticus) behavior and resource-use decisions - Wood, Tyler C; Moore, Paul A (Canadian journal of zoology, 2020)
Prey animals use the information that they extract from predator cues to assess risk. Animals can obtain information about the relative size of predators and their dietary constituents from odor cues that predators deposit in the environment. However, it is currently unknown how prey animals respond when presented with two or more pieces of information about a predator. Rusty crayfish (Faxonius rusticus (Girard, 1852)) were exposed to odors from predatory largemouth bass (Micropterus salmoides (Lacepède, 1802)) that were fed four different diets and also varied in size relative to the crayfish subjects. A series of analyses of covariance (ANCOVA) indicated that rusty crayfish altered their macrophyte consumption, foraging behavior, and shelter-use behavior depending on the relative size and dietary information presented by the largemouth bass. This study demonstrates that prey consider and respond to multiple aspects of a predatory threat when making resource-use decisions.